Individual taxpayer’s compliance during Covid-19 pandemic - Umi Sulistiyanti; Pratidina Evi Damayanti (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
The Covid-19 pandemic made economic conditions decline due to the cessation of many economic activities. The government needs the community's participation in tax compliance to restore the national economy. This study aims to analyze the effects of tax incentive policy, modernization of tax administration, religiosity, and tax awareness of taxpayers during the COVID-19 pandemic. The sample of this study is the registered individual taxpayers in the Boyolali Small Tax Office. The data of this study were collected by distributing the questionnaires to 100 respondents, in which the sample size was determined according to the Slovin formula. The data analysis methods used include multiple linear regression test, T-test, and coefficient of determination test using IBM SPSS Statistics version 25. The results of this study show that the modernization of tax administration and tax awareness have positive and significant effects on taxpayer compliance, while tax incentive policy and religiosity have no effects on taxpayer compliance.